The communication art in the extremity of the fingers: the blind person (Revista Latino-Americana de Enfermagem, 1996)
The study analyzes the communications process and its peculiarities related to a non verbal communication with blind people. The perspective answers of the blind people were observed on an Exposition of Plastic Arts for Blind people. The purpose of using this communication language was to contribute to create educations methods to these clientele. The methodology included observation, photograph record, video and personal comments. We conclude that the plastic arts are accessible to the blind by touch and give contributions to create materials, about health education using the touch. It helps the apprehension of the whole prevailing the figurative related to the aural perception.